Penerapan Teknologi Mesin AC Mobil Bagi Siswa Jurusan Teknik Otomotif Di SMK Negeri 1 Losarang - Wardika; Sunanto; Dedi Suwandi; Munengsih Sari Bunga (ISAS (Indonesian Society of Applied Science), 2021)
SMKN 1 Losarang is a vocational education institution where the level of mastery of skills is the main point in graduate output. Completeness of learning facilities and practical facilities in achieving competence in the automotive sector is certainly a necessity that must be fulfilled. By looking at a large number of students in the Automotive engineering department while the practicum facilities are still very minimal, the limited practicum facilities in supporting competency in the automotive field become an obstacle considering the ratio of the number of students to car AC trainer machines is 1:36 so that a solution is needed, namely increasing the number of facilities in the form of car AC engine trainers to improve student competence at SMK N 1 Losarang. With the application of car AC engine technology, the competence of students majoring in Automotive has increased by 20.5%. This is based on the comparison of the free test value to the post-test score that has been done